Species richness and phytogeographic affinities of rattan genus Korthalsia in Malaysia - SALWA SHAHIMI; AZI AZEYANTY JAMALUDIN; AMIRRUDIN AHMAD (Society for Indonesian Biodiversity, 2023)
Abstract. Shahimi S, Jamaludin AA, Ahmad A. 2023. Species richness and phytogeographic affinities of rattan genus Korthalsia in Malaysia. Biodiversitas 24: 5764-5778. The clustering climbing palm genus Korthalsia Blume (Arecaceae: Calamoideae: Calameae) is widespread in the Malesian region with 28 documented species. However, as many as 18 species are available in Malaysian rainforests. An inquiry was carried out in 2019 throughout Malaysia that included species richness and phytogeographic affinities for Korthalsia. Currently, Korthalsia is highly diverse in Sabah and Sarawak, with 15 species documented in this region, whereas 9 species are present in the Malay Peninsula. Species of Korthalsia were dominated by Korthalsia echinometra Becc., Korthalsia flagellaris Miq., Korthalsia hispida Becc., Korthalsia rigida Blume, and Korthalsia rostrata Blume, which suggests their prevalence in richness compared to being diverse; only 5 species found in all regions. The species accumulation curve indicates that this region's rattan community is moderately rich. There is an east-west separation for the distribution of rattan species in Peninsular Malaysia. This work's novelty reflects a new record for the distribution of K. hispida in Penang that indicates reductions in occurrence for known distributions. Perhaps underscores on significance and inadequacies related to continuous monitoring were responsible for efforts to develop a comprehensive understanding of the diversity, distribution, and potential discoveries for Korthalsia. This indicates risks from development because accessibility is improved and allows researchers to reach further terrain that previously could not be explored. However, despite this weakness, a correct checklist should be constructed for existing rainforests so Korthalsia dispersal, diversity, and richness can be correctly archived.